Effectiveness of Self-Management Supporting Programs Among People with Type 2 Diabetes Mellitus: A Systematic Review - Panchaisee, Sutthiwit (The Bangkok Medical Journal, 2025)
OBJECTIVES: This systematic review aims to evaluate the impact of self-management support programs on clinical, behavioral, and psychosocial outcomes among adults with T2DM. MATERIALS AND METHODS: This systematic review evaluates the effectiveness of self-management support programs on clinical, behavioral, and psychosocial outcomes among T2DM patients. A comprehensive literature search was conducted across PubMed, EMBASE, Cochrane Library, CINAHL, and Web of Science for randomized controlled trials (RCTs) published between 2012 and 2024. Eligible studies included adult T2DM patients participating in self-management interventions and reporting at least one relevant outcome, such as glycemic control (HbA1c), self-care behaviors, quality of life, or psychosocial factors. Methodological quality was assessed using the Cochrane Risk of Bias tool. RESULTS: Of 2,485 studies identified, 15 met inclusion criteria. Self-management support programs significantly improved HbA1c levels, with a mean reduction of 0.48% (95% CI: -0.64 to -0.32) compared to standard care. Multi-component interventions (including education, behavioral strategies, and technology support) were more effective than single-component programs. Technology-enabled interventions demonstrated comparable efficacy to traditional face-to-face programs. Culturally tailored approaches were particularly beneficial for minority ethnic groups. However, the long-term sustainability of these interventions beyond 12 months remains uncertain. CONCLUSION: Self-management support programs effectively enhance glycemic control and self-care behaviors, especially when multi-faceted, technologysupported, and culturally adapted. Future research should focus on long-term effectiveness, implementation in resource-limited settings, and standardized reporting of behavioral and psychosocial outcomes.